Analysis of genetic variation and diversity of Rice stripe virus populations through high-throughput sequencing - Huang, Lingzhe; Li, Zefeng; Wu, Jianxiang; Xu, Yi; Yang, Xiuling; Fan, Longjiang; Fang, Rongxiang; Zhou, Xueping (Frontiers in Plant Science, 2015)
Plant RNA viruses often generate diverse populations in their host plants through error-prone replication and recombination. Recent studies on the genetic diversity of plant RNA viruses in various host plants have provided valuable information about RNA virus evolution and emergence of new diseases caused by RNA viruses. We analyzed and compared the genetic diversity of Rice stripe virus (RSV) populations in Oryza sativa (a natural host of RSV) and compared it with that of the RSV populations generated in an infection of Nicotiana benthamiana, an experimental host of RSV, using the high-throughput sequencing technology. From infected O. sativa and N. benthamiana plants, a total of 341 and 1675 site substitutions were identified in the RSV genome, respectively, and the average substitution ratio in these sites was 1.47 % and 7.05 %, respectively, indicating that the RSV populations from infected N. benthamiana plant are more diverse than those from infected O. sativa plant. Our result gives a direct evidence that virus might allow higher genetic diversity for host adaptation.